Dystrophic calcifications and subcutaneous atrophy – rare complications of subcutaneous fat necrosis of the newborn - Sławińska, Martyna; Wilkowska, Aleksandra; Polkowska, Agata; Biernat, Wojciech; Domżalska-Popadiuk, Iwona; Nowicki, Roman; Sobjanek, Michał (Dermatology Review/Przegląd Dermatologiczny, 2017)
Introduction . Subcutaneous fat necrosis of the newborn is a rare form of panniculitis observed predominantly in neonates within the first weeks of life. In most cases subcutaneous lesions resolve spontaneously without complications. Occasionally, however, dystrophic calcifications and subcutaneous atrophy are observed. Objective . Presenting a case of a child with subcutaneous fat necrosis of the newborn and the clinical spectrum of the disease. Case report . We present a male neonate affected by subcutaneous fat necrosis of the newborn complicated by dystrophic calcifications and subcutaneous atrophy. Conclusions . From the clinical point of view, the most important factor to consider is the possible coexistence of subcutaneous fat necrosis of the newborn with a range of metabolic complications. The incidence of local complications (including dystrophic calcifications and subcutaneous atrophy) is rare. Patient follow-up is essential to determine future aesthetic and functional effects of the disease, and management of possible complications.